CULTURAL AND DIDACTIC ANALYSIS OF PHYSICS LEARNING: A STUDY OF THE GOOD PRACTICES OF EDUCATION IN INDONESIA AND EGYPT - Simanjuntak, Fedrik Natanuel; Novia, Loni; Vilana, Mirna; Koto, Irwan (MEDIA DIDAKTIKA, 2025)
ABSTRACT This study aims to examine and compare the practice of cultural-based and didactic physics learning between Indonesia and Egypt. This study is motivated by the importance of understanding local contexts in science education and the need to identify cross-border good practices to improve the quality of physics learning. This study uses a qualitative approach of literature study, by analyzing 50 selected literatures of 25 from Indonesia and Egypt each which include educational policies, teaching strategies, and the role of culture in physics learning. The data is categorized and compared in two main aspects: cultural and didactic. The results of the study show that Indonesia stands out in the application of contextual learning based on locality and method flexibility, while Egypt excels in curriculum consistency and strengthening of basic concepts of physics. Good practices from both countries can complement each other in creating more meaningful and relevant physics learning. This study suggests the development of physics learning that considers a balance between cultural approaches and didactic strategies. These findings are expected to be the basis for the development of curricula and learning practices that are adaptive to the diversity of global educational contexts.